SYNTHESIS AND CHARACTERIZATION OF POLY(ALKOXYPHOSPHAZENE AND ARYLOXYPHOSPHAZENE) COPOLYMERS - BAIK, HG; SOHN, YS; SUNG, YK (KOREAN CHEMICAL SOC, 1992)
Copolymers with two different side groups, 2,2,2-trifluoroethoxy and p-chlorophenoxy groups, have been synthesized by reaction of poly(dichlorophosphazene) with their sodium salts, and characterized by elemental analysis, gel permeation chromatography, IR and NMR spectroscopies. The molecular weight measurement has shown that the weight average molecular weight, MBAR(w) of the copolymers are all above 10(6) and their molecular weight distributions are monomodal and narrow (MBAR(w)/MBAR(n)<4). Thermal properties of these copolymers measured by DSC and TGA exhibited to be intermediate between those of the two corresponding homopolymers.
Keywords: PHOSPHAZENE; POLYPHOSPHAZENES; CHEMISTRY